Superficial Spreading Squamous Cell Carcinoma Endometrium andIcthyosis Uteri with CINIII with p16 Expression:Report of 2 Unusual Cases - Neelam Sood; Kumar Sharad Sinha (Journal of Krishna Institute of Medical Sciences University, 2017)
We report two interesting and rare case reports, a 60 year old with well differentiated squamous cell carcinoma of cervix with superficial spreading into the endometrium, other female of 70 year old with features of CIN III also involving the endometrium with multilfocal epidermidization consistent with icthyosis uteri, involving cervix and endometrium. p16 was used as a surrogate marker which was positive for neoplastic cells in both the cases, showing HPV aetiology. Superficial spreading squamous cell carcinoma of the cervix is a rare entity, with less than 30 cases reported in the literature. Primary endometrial squamous cell carcinoma usually occurs in postmenopausal women with mean age of presentation being 67 years. It is postulated that tumour may arise from ichthyosis uteri. Demonstration of p16 positivity in tumour cells helps in revealing HPV aetiology was also confirmed thus signifying its usefulness. Hence, we report these rare entities.